2022
DOI: 10.1002/jcv2.12116
|View full text |Cite
|
Sign up to set email alerts
|

The effect of perinatal interventions on parent anxiety, infant socio‐emotional development and parent‐infant relationship outcomes: A systematic review

Abstract: Background Infants of parents with perinatal anxiety are at elevated likelihood of experiencing disruption in the parent‐infant relationship, as well as difficulties with socio‐emotional functioning in later development. Interventions delivered in the perinatal period have the potential to protect the early dyadic relationship and support infants’ ongoing development and socio‐emotional outcomes. This review primarily aimed to examine the efficacy of perinatal interventions on parent anxiety, infant socio‐emot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 165 publications
(374 reference statements)
1
14
0
Order By: Relevance
“…These have generally focused on increasing child-caregiver contingency (even though observational studies, as described above, have suggested that anxiety can be characterised as a mix of excessive contingency in some circumstances and insufficient in others). Interventions that target caregiver-child interactions have been shown to lead to changes in adult anxiety symptoms as well as changes in interactional style (C. G. Smith et al, 2022b). Findings are in line with transactional models of intervention that highlight the importance of integrating both caregivers and children into treatment programmes, on the basis that socio-emotional difficulties in one partner tend to exacerbate difficulties in the other.…”
Section: Anxietysupporting
confidence: 62%
See 2 more Smart Citations
“…These have generally focused on increasing child-caregiver contingency (even though observational studies, as described above, have suggested that anxiety can be characterised as a mix of excessive contingency in some circumstances and insufficient in others). Interventions that target caregiver-child interactions have been shown to lead to changes in adult anxiety symptoms as well as changes in interactional style (C. G. Smith et al, 2022b). Findings are in line with transactional models of intervention that highlight the importance of integrating both caregivers and children into treatment programmes, on the basis that socio-emotional difficulties in one partner tend to exacerbate difficulties in the other.…”
Section: Anxietysupporting
confidence: 62%
“…individual observations, several months apart), and using a technique such as dynamic structural equation modelling, include genetic risk as a covariate by examining specific alleles that contribute to polygenic risk scores for anxiety but which are not shared between children and caregivers (Birmaher et al, 2022). Other approaches are to study special populations, such as caregivers raising genetically unrelated children (Harold et al, 2013), and interventions that specifically target child-caregiver behaviours to examine the long-term development of symptoms in the child (C. G. Smith et al, 2022a).…”
Section: Part 1 -Methods -How Can We Study Atypical Interactions?mentioning
confidence: 99%
See 1 more Smart Citation
“…Important theoretical and practical insights into causal mechanisms can also come from intervention studies that target caregiver–child interaction—although clinical interventions tend to be relatively broad brush‐stroke (e.g. targeting aspects of the caregiver mental health symptoms on their own, as well as the caregiver–child interaction; Smith et al., 2022). This means that, when an intervention is effective, it can be hard to impute to underlying mechanisms.…”
Section: Part 1—methods—how Do We Study Child–caregiver Interaction D...mentioning
confidence: 99%
“…Another would be to measure caregiver–child interaction repeatedly across multiple time points and, using a technique such as dynamic structural equation modelling, include genetic risk as a covariate by examining specific alleles that contribute to polygenic risk scores for anxiety but which are not shared between children and caregivers (Birmaher et al., 2022). Other approaches are to study special populations, such as caregivers raising genetically unrelated children (Harold et al., 2013), and interventions that specifically target child–caregiver behaviours to examine the long‐term development of symptoms in the child (Smith et al., 2022).…”
Section: Part 1—methods—how Do We Study Child–caregiver Interaction D...mentioning
confidence: 99%